Monitoring during extracorporeal membrane oxygenation. Issue 3 (June 2016) - Douflé, Ghislaine; Ferguson, Niall D.
Abstract : Purpose of review: An increasing number of patients are placed on extracorporeal membrane oxygenation (ECMO) for respiratory or cardiac failure. Sound understanding of physiology and configuration of ECMO is essential for proper management. This review covers different monitoring parameters and tools for patients supported with different types of ECMO. Recent findings: Emphasis is placed on monitoring saturations at different sites depending on type of ECMO support. The main monitoring tools detailed in this review are echocardiography and pulmonary artery catheters. Summary: The review will help physicians better assess adequate ECMO support by using the appropriate parameters for each type of configuration.